Analysis Some Risk Factors on Brain Cancer Disease by Using Factor Analysis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Brain cancer is the cancer of the central information-processing center of the body.  Brain tumour can be malignant or benign, and can occur at any age. Only malignant tumors are cancerous. A primary brain tumor initially forms in the brain tissue. In addition, the aim of this study is to investigate the most important factors affecting on the brain cancer and identify the demographic of the disease of brain cancer, then factor analysis has been used to identify factors affecting brain cancer, The methods of this study was used descriptive statistics and factor analysis, then Factor Analysis (FA) is an exploratory technique applied to a set of observed variables that seeks to find underlying factors (subsets of variables) from which the observed variables were generated. Moreover, recorded data for brain cancer were taken from Hiwa Hospital in Sulaymaniyah Governorate during the period of (2018 to 2020). 150 patients and 8 variables were included in the study. After analysis study detected from factor which are explain 59.036% of the variance, and the result identified three factors such that,1stFactor: This factor containing these variables (Age, Weight) by total variance 21.400%,  2ndFactor: This factor containing these variables (Gender, Smoking and Occupation) by total variance 20.665%, 3rdFactor: This factor containing the variable (Governorate, Blood type and Drinking) by total variance 16.971%, The papers limitation is including lack of variables taken for brain cancer and the number of samples was insufficient. Finally, the rate of 59.036% aforementioned variables influence on the brain cancer.